2010
DOI: 10.4161/cc.9.3.10591
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog proteins activate pro-angiogenic responses in endothelial cells through non-canonical signaling pathways

Abstract: The Hedgehog (Hh) pathway orchestrates developmental and homeostatic angiogenesis. the three Hh isoforms--Sonic Hedgehog (Shh), Indian Hedgehog (Ihh) and Desert Hedgehog (Dhh)--signal through patched-1 (ptCH1) and Smoothened (SMo), to activate the Gli transcription factors with a characteristic rank of potency (Shh >> Ihh > Dhh). To dissect the mechanisms through which Hh proteins promote angiogenesis, we analyzed processes inherent to vessel formation in endothelial cells. We found that none of the Hh ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
203
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(215 citation statements)
references
References 29 publications
11
203
0
1
Order By: Relevance
“…However, all three hedgehog proteins promote endothelial cell tubulogenesis in 3D cultures in a Smo-dependent manner (Polizio et al, 2011). Consistent with the required cytoskeletal rearrangement for tubulogenesis, Shh, Ihh and Dhh all stimulate the small GTPase RhoA and actin stress fibers formation (Chinchilla et al, 2010). This effect, mediated by Smo and G proteins, defines a new non-canonical hedgehog pathway.…”
Section: Sonic Hedgehog Signaling: Components Routes and Mechanismmentioning
confidence: 83%
See 1 more Smart Citation
“…However, all three hedgehog proteins promote endothelial cell tubulogenesis in 3D cultures in a Smo-dependent manner (Polizio et al, 2011). Consistent with the required cytoskeletal rearrangement for tubulogenesis, Shh, Ihh and Dhh all stimulate the small GTPase RhoA and actin stress fibers formation (Chinchilla et al, 2010). This effect, mediated by Smo and G proteins, defines a new non-canonical hedgehog pathway.…”
Section: Sonic Hedgehog Signaling: Components Routes and Mechanismmentioning
confidence: 83%
“…Another non-canonical Shh signaling mainly controls endothelial cells cytoskeletal reorganization and fibroblast migration through activating small GTPases and regulating fluctuations of calcium ions upon stimulation of Shh (Chinchilla et al, 2010; El-Zaatari et al, 2010; Polizio et al, 2011). It has been demonstrated that none of the three hedgehog ligands are able to induce Gli-target genes in human umbilical vein (HUVeC) or human cardiac microvascular endothelial cells (HMVeC), indicating that endothelial cells do not respond to hedgehog through the canonical pathway.…”
Section: Sonic Hedgehog Signaling: Components Routes and Mechanismmentioning
confidence: 99%
“…Recently, the immediate signaling partner of Ptch, Smo, was shown to be dispensable for adult HSC differentiation and specification of the T cell lineage (27). The discrepancy between the role of Smo and its immediate signaling partner Ptch in T cell development can be explained by the fact that Ptch also acts on molecular processes without the involvement of the Smo/Gli axis (28)(29)(30). For example, it was demonstrated that Ptch functions as a dependence receptor, which induces apoptosis in the absence of Hh, whereas its proapoptotic activity is blocked the presence of Hh (29).…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition to the Glidependent canonical Hh pathway, the binding of Hh ligands with Ptch also activates several noncanonical pathways such as Rho small GTPases and phosphoinositide 3-kinase (PI3K)/Akt pathways. 13,14 We have found that IR did not activate Hh/Gli signaling, whereas transient activation of the Hh pathway in salivary gland by inducible expression of Shh transgene in Keratin5…”
Section: Introductionmentioning
confidence: 99%